Transformations of aldimines derived from pyrrole-2-carbaldehyde.: Synthesis of thiazolidino-fused compounds - Aydogan, F; Öcal, N; Turgut, Z; Yolacan, C (KOREAN CHEMICAL SOC, 2001)
4-Thiazolidinones which are hetarylsubstituted at thr 2-position were prepared by the reaction of mercapto acids with aldimines which were prepared by the condensation of pyrrole-2-carbaldehyde with different aromatic amines. After their benzylidene derivatives were obtained, we first applied the Wittig reagent on them in the presence of triethylamine, dihydrofurothiazolidines were synthesized. Second, we prepared new pyrazolinothiazolidines by using phenylhydrazine in the presence of sodium acetate. All mentioned compounds have been characterized by their spectral data, and screened for their antimicrobial activities. Some of them exhibit moderate to good antibacterial and tuberculostatic activities.
Keywords: pyrrole-2-carbaldehyde; 4-thiazolidinone; benzylidene derivatives; dihydrofurothiazolidines; pyrazolinothiazolidines; Chemistry